2020
DOI: 10.1002/14651858.cd010022.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol intake reduction for controlling hypertension

Abstract: Data collection and analysisTwo review authors independently assessed search results and extracted data using standard methodological procedures adopted by Cochrane.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…In this study, a meta-regression model indicated a decrease of 0.91 mm Hg in systolic and 0.75 mm Hg in diastolic blood pressure per one drink per day. A Cochrane review was set by Acin et al to examine the effects of interventions to reduce alcohol intake on blood pressure for at least 3 months [ 111 ]. Results of the analysis were primarily determined by the randomized controlled trial reported in reference [ 109 ].…”
Section: Effects Of Alcohol Withdrawal In Hypertensionmentioning
confidence: 99%
“…In this study, a meta-regression model indicated a decrease of 0.91 mm Hg in systolic and 0.75 mm Hg in diastolic blood pressure per one drink per day. A Cochrane review was set by Acin et al to examine the effects of interventions to reduce alcohol intake on blood pressure for at least 3 months [ 111 ]. Results of the analysis were primarily determined by the randomized controlled trial reported in reference [ 109 ].…”
Section: Effects Of Alcohol Withdrawal In Hypertensionmentioning
confidence: 99%
“…5 Intervention studies have generally been conducted as short-term randomized controlled trials that investigated the BP effects of reduced alcohol intake in adults with a high alcohol intake. 5,[7][8][9] The body of evidence detailing the effects of changes in alcohol intake on systolic blood pressure (SBP) and diastolic blood pressure (DBP) in persons who were initially consuming light to Hypertension. 2023;80:1961-1969.…”
mentioning
confidence: 99%
“…(2) The diagnostic criteria for dyslipidemia involved a physician's diagnosis of dyslipidemia, use of lipid-lowering medications, total cholesterol (TC) levels ≥ 6.22 mmol/L, triglycerides (TG) levels ≥ 2.26 mmol/L, high-density lipoprotein cholesterol (HDL-C) levels < 1.04 mmol/L, or low-density lipoprotein cholesterol (LDL-C) levels ≥ 4.14 mmol/L [ 29 , 30 ]. (3) Alcohol consumption is defined as consuming alcohol within the past month and consuming alcohol at least once per week [ 31 , 32 ]. (4) Insufficient sleep is characterized by a duration of less than 7 h per day [ 33 , 34 ].…”
Section: Methodsmentioning
confidence: 99%